Free space attenuation analysis for X -band and S-band satellite link using meteorological radar data in the tropics - Badron, Khairayu; Ismail, Ahmad Fadzil; Basri, Atikah Balqis; Abdul Halim, Syafrina; Ismail, Maszlan Yusof B.; Salim, Hamid (UiTM, 2017)
Free space fading for satellite link propagation studies in the equatorial regions are indeed particularly scarce, complicated and expensive to venture upon. Most of satellite propagation studies done in temperate climate are not reasonable for countries in the equatorial region due to its huge climate differences. In equatorial regions, the future stratospheric and space-based telecommunications systems are expected to operate with high elevation angle slant paths and high frequency of operation from the Earth stations’ point of view. These systems will also be sharing frequency bands with other terrestrial and space services. From this standpoint, a precise modelling of the vertical variation of free space path loss parameters will be of great interest for improving the prediction of the clear sky margin along the slant path in the tropics. In this paper, the Free Space Path Loss (FSPL) propagation link for Xband and S-band RazakSAT satellite will be analysed using a Terminal Doppler Weather Radar (TDWR) data. Both links will be evaluated and the assessment of the link’s fade margin will be suggested. An accurate estimation of the satellite fade margin will evidently save power from the satellite perspective and better transmission can be estimated. The outcome of this research will be very useful for future implementation of satellite link fade margin improvement during non-rain weather, both during clear sky and cloudy weather in the tropical region. This research will facilitate the key decision makers and the satellite designers to progress business, availability, and throughput proficiently. Therefore, hopefully, the spending is well reasonable with a better return on investment (ROI) and attracts more investors in satellite industries.